Hubungan Driving forces, Pressure, State, Exposures, health Effects, Action (DPSEEA) dalam Lingkup Health Impact Assessment (HIA) - Winda Trijayanthi Utama (Fakultas Kedokteran, 2020)
The definition of Driving Forces, Pressure, State, Exposures, Health Effects, and Action (DPSEEA) is a framework that represents descriptively the way in which the various driving forces generate pressures that affect the state of human health and the environment, through the various exposure pathways where people come into contact with the environment. The DPSEEA framework is used to see the relationship between several factors affecting health and the environment more clearly. Actions taken can be implemented at several points in the framework and can take many forms, for example: development policies, health education, medication, control and measurement techniques. The relationship between DPSEEA in the Health Impact Assessment (HIA) is that DPSEEA displays various levels of action that can reduce these health impacts, then DPSEEA can be developed for most of the health risk factors and for the outcomes related to health itself. Keywords: Driving Forces, Pressure, State, Exposures, Health Effects, and Action; Health Impact Assessment